IMPLEMENTASI MULTIDIMENSIONAL POVERTY INDEX DALAM MENGUKUR KEEFEKTIVITASAN PENGUKURAN KEMISKINAN DI INDONESIA - Putri, Salshabilla Herdyanti Martoni; Shofwan (Journal of Development Economic and Social Studies, 2024)
So far, measuring poverty in Indonesia still refers to the Poverty Line (GK) approach carried out by the Badan Pusat Statisitk (BPS), which is the institution given the authority to calculate poverty rates. Meanwhile, the problem of poverty today is no longer uni-dimensional but multidimensional. This research was conducted with the aim of applying the Multidimensional Poverty Index (MPI) in measuring the effectiveness of measuring the Poverty Line (GK) approach in Indonesia. Then, this research provides an outline of the advantages and disadvantages of poverty measurement in Indonesia and analyzes the effectiveness of poverty measurement by applying the Multidimensional Poverty Index (MPI). After that provides recommendations for policy makers regarding the most appropriate poverty measures.